Menstruation Related Practices among Adolescent Girls and Women in a Semi-urban Area of Nepal - Singh Bhandari, Mukta; Chataut, Jagdish; Tamrakar, Dipesh; Shrestha, Abha; Lhaki, Pema (Journal of College of Medical Sciences-Nepal, 2024)
Background Menstruation is often associated with restrictions from different activities. Studies about extreme form of menstruation practices i.e. “Chhaupadi” have been widely done but other practices have been less studied. Thus, this study aimed to find out the menstruation related practices among adolescent girls and women in secondary schools in a semi-urban community of Nepal. Methods This was a descriptive cross-sectional study done at two secondary schools in a semi-urban community of Panauti municipality which were selected purposively. The duration of study was from 31st October 2022 to 15th November, 2022. Total 158 adolescent girls and women present at the study site who have had menarche were included in the study through census sampling. Ethical approval was taken from the Institutional Review Committee [Reference number: 36/22] of Kathmandu University School of Medical Sciences. Self-administered semi-structured questionnaires were used to collect the information. Results Among 158 study participants, menstrual restriction practice was followed by 155(98.66%) and most common restriction was not being allowed to worship or go to worshipping room 150 (96.77%). Most (68.98%) of the study participants said that their mother insisted them to follow such practices. Conclusions Menstruation related practices were common among the study participants and most common form of restriction was not being allowed to worship.